Adynamic Graciloplasty for Faecal Incontinence in an Adult after Anal Atresia Correction in Infancy – a Case Report - Samalavicius, Narimantas Evaldas; Nutautiene, Vitalija; Butenaite, Lina; Markelis, Rytis; Dulskas, Audrius (Lietuvos chirurgija, 2020)
Background. Here we present a case of female patient suffering from bowel incontinence. Case report. The patient underwent unstimulated graciloplasty. Postoperative period was uneventful. After 4 weeks, a course of low frequency electric external stimulation in the area around the neurovascular bundle in the thigh was performed. Patient was evaluated 3 months postoperatively. On inspection, her anus was closed at rest. She stated moderate improvement in her continence and quality of life, her Wexner score was 10 and FISI score was 32 (prior surgery 19 and 44 accordingly). Conclusion. Adynamic graciloplasty seems to be a reasonable method of choice for faecal incontinence.